Alternative segmentation approaches for user typology profiling in gamified system, designed for company employee usage - Mushmov, Apostol; Boevsky, Ivan; Avramov, Victor (Leadership, Society, Strategic Visions, 2021)
We could profi le the employee of a company in many different ways. Nevertheless, when talking about gamifi ed system for employee motivation, there is a specifi c profi ling that could be done in terms of people being in a game like circumstances. In this research we propose some alternative approaches for such system, user’s profi ling and the results are interpreted as well as the advantages and disadvantages are discussed in relation to future system improvement.